Wood defects - Hanafi, Siti Fadzilah (2009)
Wood has higher value and is very important to world economy. It is used as raw material, fuel or industrial raw material in the several part of the world. But wood defects can degrade the value of wood. Bad wood defects can make our industry flinch. Example of wood defects have occur from three major such as natural wood defects, defect due to processing and effect of drying defects on machining. So, the best way to get the quality wood is control drying using special schedule and to person who handle the machine should be more careful. Proper treatments of wood defects can prevent from further deterioration and also that can improve the grade and value of wood.